Russian Scheme for Resumption of Specie Payments (Quarterly Journal of Economics, 1897)
Journal Article Russian Scheme for Resumption of Specie Payments Get access The Quarterly Journal of Economics, Volume 11, Issue 2, January 1897, Pages 212–214, https://doi.org/10.1093/qje/11.2.212 Published: 01 January 1897